Lobbying Activities and Insider Trading - King, Raymond D.; O'Keefe, Terrence B. (The Accounting Review, 1986)
[This study tests whether there is a relationship between the lobbying activities of firms on a proposed accounting standard (FAS No. 19) and the trading activities of corporate insiders. We find that, on average, insiders of full cost firms that lobbied were net sellers and successful efforts lobbiers were net buyers, while non-lobbiers took opposite positions. The results are consistent with the hypothesis that lobbying activity is correlated with management's expected wealth. The results are also consistent with comment letters to the FASB having information value, since insiders trade on their personal account in the same direction their firms lobby. Alternatively, the results can be interpreted as support for the conclusion of Larcker, Reder and Simon [1983] that FAS No. 19 was perceived to have economic consequences.]